2009
DOI: 10.1103/physreve.79.061904
|View full text |Cite
|
Sign up to set email alerts
|

DNA electrophoresis in a sparse ordered post array

Abstract: We present a study of the electrophoresis of long DNA in a strong electric field through a hexagonal array of cylindrical microscale posts spaced such that the pore size is commensurate with equilibrium coil size of the DNA. Experimental mobility, dispersivity, and videomicroscopy data indicate that the DNA frequently collide with the posts, contradicting previous Brownian dynamics studies using a uniform electric field. We demonstrate via simulations that the frequent collisions, which are essential to separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
57
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 36 publications
(64 citation statements)
references
References 31 publications
6
57
1
Order By: Relevance
“…In contrast to the predictions of these simulations, experimental observations of DNA electrophoresis in a hexagonal array of 1 µm diameter posts with 3 µm center-to-center spacing showed that frequent DNA-post collisions do occur in an ordered array at this post density [17]. Moreover, Brownian dynamics simulations that included the perturbations in the electric field caused by insulating posts matched the experimentally measured electrophoretic mobility [17,18], indicating that the disturbance in the electric field due to the posts qualitatively alters the transport in this relatively tight array.…”
contrasting
confidence: 84%
“…In contrast to the predictions of these simulations, experimental observations of DNA electrophoresis in a hexagonal array of 1 µm diameter posts with 3 µm center-to-center spacing showed that frequent DNA-post collisions do occur in an ordered array at this post density [17]. Moreover, Brownian dynamics simulations that included the perturbations in the electric field caused by insulating posts matched the experimentally measured electrophoretic mobility [17,18], indicating that the disturbance in the electric field due to the posts qualitatively alters the transport in this relatively tight array.…”
contrasting
confidence: 84%
“…In prior work on the collision with a small cylindrical obstacle [13,29], the predictions using this level of coarse graining agree well with experimental data. In order to emphasize the role of the obstacle shape, our elliptical obstacle has a semi-major axis a 5 1.3 mm and semi-minor axis b 5 0.7 mm.…”
Section: Brownian Dynamicssupporting
confidence: 68%
“…Using reasonable values for the physical parameters [9,28], this Péclet number implies an electric field around 60 V/cm. Our electric field is strong but still within the range of electric fields used in recent experiments and simulations [29].…”
Section: Brownian Dynamicsmentioning
confidence: 94%
“…This conclusion was at odds with experimental work demonstrating separations in such arrays, 6 and the disagreement between simulation and experiment was ultimately resolved by recognizing that the curved field lines in electrically (and ionically) insulating post arrays break up the channeling effect to some extent. 15 The channeling effect described in simulations only dominates when the array is so sparse that the electric field lines are hardly perturbed by the posts. 16 However, since transport across field lines occurs by diffusion, the effects of channeling seem to limit separations in sparse arrays to electric fields in the range of 10-20 V/cm.…”
Section: Introductionmentioning
confidence: 99%
“…3 Unfortunately, due to the slow migration of long DNA in the net direction of the applied field, pulsed field separations take hours to days to achieve a baseline separation; 3 this time is compared to minutes needed to separate long DNA in post arrays. [4][5][6] Regular arrays of micro-and nano-sized posts, fabricated by semiconductor methods, have been the subject of substantial experimental work [6][7][8][9][10][11][12][13][14][15][16][17][18][19] using a wide variety of materials, post sizes, and post spacing. In addition to microfabricated arrays with perfectly ordered features, results also exist for self-assembled magnetic beads, 4,5,20 which form quasihexagonal arrays, microfabricated arrays with intentional disorder, 21 and nanowire-based posts.…”
Section: Introductionmentioning
confidence: 99%